Analysis of non-geometric accuracy effects of articulated robots. Issue 5 (21st August 2017) - Lux, Gregor; Ulrich, Marco; Baker, Thomas; Hutterer, Martin; Reinhart, Gunther
Abstract : Purpose: Articulated robots are widely used in industrial applications owing to their high repeatability accuracy. In terms of new applications such as robot-based inspection systems, the limitation is a lack of pose accuracy. Mostly, robot calibration approaches are used for the improvement of the pose accuracy. Such approaches however require a profound understanding of the determining effects. This paper aims to provide a non-destructive analysis method for the identification and characterisation of non-geometric accuracy effects in relation to the kinematic structure for the purpose of an accuracy enhancement. Design/methodology/approach: The analysis is realised by a non-destructive method for rotational, uncoupled robot axes with the use of a 3D lasertracker. For each robot axis, the lasertracker position data for multiple reflectors are merged with the joint angles given by the robot controller. Based on this, the joint characteristics are determined. Furthermore, the influence of the kinematic structure is investigated. Findings: This paper analyses the influence of the kinematic structure and non-geometric effects on the pose accuracy of standard articulated robots. The provided method is shown for two different industrial robots and presented effects incorporate tilting of the robot, torsional joint stiffness, hysteresis, influence of counter balance systems, as well as wear and damage. Practical implications: Based on these results, an improved robot model for a better match between the mathematical description and the real robot system can be achieved by characterising non-geometric effects. In addition, wear and damages can be identified without a disassembly of the system. Originality/value: The presented method for the analysis of non-geometric effects can be used in general for rotational, uncoupled robot axes. Furthermore, the investigated accuracy influencing effects can be taken into account to realise high-accuracy applications.